Stock Price Movement Through Technical Analysis: Empirical Evidence from the Information Technology Sector - Vasantha, S.; Dhanraj, V.; Varadharajan, R. (Indian Journal of Finance, 2012)
Technical analysis is the study of historic price movements of securities, trading volumes, and market action, primarily through the use of charts for the purpose of forecasting future price trends. Through technical indicators, investors can analyze the short-term price movement of the stock, the most important market turning points and project the price movement .This paper attempts to apply technical analysis on five selective stocks of the Information technology sector such as Tata Consultancy Services (TCS), Hindustan Computers Limited Technologies (HCL), Infosys, Wipro and Polaris, which would help the investors to identify the current trends and risks associated with the scrip at par with the market. This study is only based on secondary data which had been collected from NSE website, journals and magazines. The technical indicators have been analyzed by using twelve months share prices of the companies, which was for the period of January - December 2011. The various techniques such as Relative Strength Index, Bollinger Bands, Moving Average Convergence Divergence and Simple Moving Average were used to take a decision on whether to buy or sell the stocks of the IT sector.